The African Small Island Developing States and normative coherence for sustainable development: The quality of civil rights and liberties. (22nd March 2022) - Graham, Victoria; Graham, Suzanne
Summary: Motivation: The literature on small states suggests that small island states are more likely than larger states to support regional and international democratic norms, but is this true of the six African Small Island Developing States (ASIDS), an underexplored regional grouping? This article explores the ASIDS' normative commitment to regional democratic norms of civil rights and liberties. Purpose: This article aims to answer the question: how normatively coherent are ASIDS with the normative development of regional civil rights and liberty norms promoted by the African Union (AU) through the Banjul Charter? Methods and approach: The article adopts a normative conceptual lens in its outlook and uses quality of democracy methodology to compare the quality of selected regional civil rights and liberty norms across the ASIDS grouping. Findings: The article finds that procedurally all ASIDS are coherent with the Banjul Charter norms on civil rights and liberties, but that local realities mean that substantive coherence to these norms is often slow or, in some cases, ineffectual. Cultural context, agency, and capacity are as important as size and "islandness" in determining small island state democratic quality. Policy implications: It suggests that political will for normative coherence for sustainable development (NCSD) within a region is not enough, at least for these island states. A real lack of capacity warrants greater regional support from continental Africa in the form of, among other things, financing, capacity building, expertise, peer review, and monitoring. Only through reinforcement of NCSD can the AU fulfil its rights‐based mission.